THE CONFLICT OF AZERBAIJAN AND ARMENIA WITH SPECIAL REFERENCE TO NAGORNO KARABAKH: AN OVERVIEW - Mumim Ahmad khan (Universitas Islam Negeri Raden Fatah Palembang, 2021)
Every conflict and war has a pre-history, such as Nagorno-Karabakh conflict is one of them. In the current scenario, the Nagorno-Karabakh has become the centre of international politics. The article focuses on the conflicts of Nagorno Karabakh, about its actual geo-location, integrity, and sovereignty. Also, in this study, we have tried to highlight the political agenda of the world’s top leading countries like Russia and France was backed by Armenia. At the same time Turkey, Malaysia, Pakistan, and Israel supported Azerbaijan. On 10th November 2020, after six weeks of fierce fighting, Armenia and Azerbaijan agreed to end the military operation over the Nagorno-Karabakh dispute, the ceasefire brokered by Russian President Vladimir Putin. Armenian leader Nikol Pashinyan has described the decision to agree on a ceasefire as ‘painful’ for him and their citizens, while Azerbaijan’s President Ilham Aliyev has claimed victory. Perhaps, the objective of the full involvement of Turkey in this fight was to give a signal of emerging as a leading country in the Muslim World. The ceasefire was organized by Russia between Armenia and Azerbaijan, which keeps Turkey and western countries out of the final peace talk, which seems like Russia wants to show remains a dominant power and its impact in the South Caucasus.